The effect of virtual interactive nurse-led support group intervention on fatigue, shock anxiety, and acceptance of implantable cardioverter defibrillator patients: a randomized trial - Masoume Rambod; Samira Rohaninasab; Nilofar Pasyar; Mohammad Hossein Nikoo (BMC Cardiovascular Disorders, 2024)
Abstract Background Implantable cardioverter defibrillators (ICD), as a gold and standard treatment for fatal cardiac arrhythmia, may lead to some physical and psychological problems for the patients. Therefore, performing some interventions to reduce or eliminate these issues is crucial. This study aimed to determine the effect of virtual interactive nurse-led support group intervention on fatigue, shock anxiety, and acceptance of ICD patients. Methods This is a clinical trial study on 72 patients with ICD. They were randomly allocated to the intervention (n = 36) and control (n = 36) groups. A virtual interactive nurse-led support group intervention through WhasApp was performed for one month. Multidimensional fatigue inventory, Florida Shock Anxiety Scale, and Florida Patient Acceptance Scale were used. Data were analyzed to perform the analysis of data through SPSS, using independent and paired-t test, Mann-Whitney U test, Wilcoxon test, and ANCOVA. Results Before the intervention, no significant difference was observed between the two groups with regard to fatigue, shock anxiety, and ICD acceptance. However, after the intervention, a significant difference was found between the two groups with regard to fatigue, shock anxiety, and ICD acceptance (P < 0.05). Conclusion This study showed that virtual interactive nurse-led support group intervention reduced fatigue and shock anxiety and improved the ICD acceptance. Practice implications This flexible, accessible, and interactive nurse-led support group intervention is suggested to be used for ICD patients. Trial registration This trial was registered and approved by Iranian Registry of Clinical Trials (Trial Id: 60,738, date: (24/02/2022). ( https://www.irct.ir/trial/60738 ).